shRNA-mediated Slc38a1 silencing inhibits migration, but not invasiveness of human pancreatic cancer cells - Xie, Jing (AME Publishing Company, 2013)
OBJECTIVE: Early metastasis is a major biological feature of pancreatic cancer. The current study examined whether silencing Slc38a1, a gene involved in energy metabolism, using short hairpin RNA (shRNA) could inhibit the growth, migration, and invasiveness of pancreatic cancer cells. METHODS: A series of Slc38a1 shRNAs were designed and cloned into the pGPU6/GFP/Neo vectors. An shRNA with the most efficacious inhibitory action on SCL38A1 expression (65% inhibition) upon screening in DH5α bacteria was used to transfect SW1990 human pancreatic cancer cells. Cell growth, migration, and invasiveness were examined using cell counting kit-8, Boyden chamber without and with Matrigel, respectively. RESULTS: Transfection of SW1990 cells with the SLCs38A1 shRNA significantly decreased the proliferation (P<0.0001) and migratory potential (by 46.7%, P=0.0399) of the cancer cells. Invasiveness, however, was not affected. CONCLUSIONS: Inhibiting Slc38a1 using shRNA technology could decrease the growth and migration of representative pancreatic cancer cells. However, the fact that invasiveness was not affected suggested that SLC38A1 is unlikely to be responsible for early metastasis.